2021
DOI: 10.1111/scd.12557
|View full text |Cite
|
Sign up to set email alerts
|

Oral health needs of athletes with intellectual disability in Southern Europe: Greece, Italy and Spain

Abstract: Aims The population with intellectual disabilities (ID) has been reported to be a vulnerable population in terms of oral health. The aims of this study were to evaluate the oral condition and treatment needs of Special Olympics (SO) athletes from Greece, Italy and Spain. Methods and results A cross‐sectional study was performed with data collected in annual SO events held in Greece, Italy and Spain, between 2010 and 2012. The recorded parameters were the presence/absence of edentulism, untreated decay, filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 36 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…Regarding the overall low percentage of subjects with sealants on permanent teeth, it is important to note that since 2018, the SO-SS program in Romania includes professional cleaning and provision of glass-ionomer sealant, which considerably increased the proportion of subjects with sealants during the last two SS events. Data reported in other studies on SO athletes of similar ages also showed that the presence of sealants among athletes with ID was the least frequent of the oral findings [ 5 , 12 , 14 , 15 , 16 ]. The low prevalence of fissure sealants points out a persistent need for prevention.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Regarding the overall low percentage of subjects with sealants on permanent teeth, it is important to note that since 2018, the SO-SS program in Romania includes professional cleaning and provision of glass-ionomer sealant, which considerably increased the proportion of subjects with sealants during the last two SS events. Data reported in other studies on SO athletes of similar ages also showed that the presence of sealants among athletes with ID was the least frequent of the oral findings [ 5 , 12 , 14 , 15 , 16 ]. The low prevalence of fissure sealants points out a persistent need for prevention.…”
Section: Discussionmentioning
confidence: 55%
“…Trihandini et al [ 4 ] reported untreated decay in more than 70% of a group of 1217 Indonesian SO athletes (mean age = 13.46 ± 2.97 years). In South European countries, the percentage of SO athletes with untreated caries varied between 38.1% (Spain), 46.5% (Greece), and 48.5% (Italy) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations